Alveolar Ridge Augmentation with Custom 3d-printed Block Graft: Case Report - Camilla Alves Janott Sarlo; Kamila Rodrigues do Valle Temponi; Júlia Cardoso Santos Alvarenga; Juliana Fiaux Campanelle Ribeiro Borges; Alexandre Campos Montenegro; Gonçalo Sobreiro Pimentel Neto (Portal de Periódicos da Marinha do Brasil, 2023)
The use of the technology CAD/CAM (computer aided design/computer aided manufacturing) and 3D (three dimensional) to alveolar reconstructions in implant dentistry allows detailed preoperative planning, the design of the desired grafting result, and the virtual evaluation of the result in relation to the prosthetic reconstruction. This paper aims to details the synthetic bone graft made through this technology, followed by the installation of osseointegrated implants and prosthetic rehabilitation in a bone imperfection in the jaw. A 22-year-old man attended the clinic due to a tooth avulsion of the four lower incisors with significant vertical bone loss of alveolar ridge. Because of the extensive bone loss, it was made a prototyped printed block graft. The intraoral scan and the generated image files were sent to the virtual planning center. First, it was necessary a surgery to install the block graft. After the healing process, it was made a surgery to put two osseointegrated implants. Three months later, temporary fixed prostheses on implants were made to conditioning the peri-implant soft tissues and the progressive loading of the implants. The increase of the alveolar ridge using personalized printed block graft was presented as a technique with numerous advantages, since it does not require a donor site, reduces the surgical time and presents perfect adaptation of the block to the bone imperfection, resulting in a less postoperative morbidity. This technique is indicated to cases of severe bone imperfections, aims to optimize results, and provide less discomfort to the patient.